Tendances Technico-Tactiques du Karate Al Gerein de Haut Niveau : épreuve de Kumité - Khaled, Hamida (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2015)
The Algerian Karate is in a very critical phase in its history in terms of achieving results across the world championships. The present work will try to highlight trends in the practice of technical and tactical point of view and at the same to release specific to Algerian specificities (if any) in comparison with the level. This approach will perhaps diagnose actual failures and at the same wear as appropriate.
يمر الكراتي في الجزائر بمرحلة حرجة في تاريخه خاصة فيما يتعلق بتحقيق النتائج على مستوي بطولات العالم. تهدف هذه الدراسة إلى إظهار اتجاهات هذه الممارسة من الناحية التقنية التكتيكية وبالتالي إظهار الخصوصيات التي يمتاز بها الرياضيون الجزائريون (إن وجدت) مقارنة بالمستوى العالمي. هذه المقاربة قد تسمح بتشخيص الاختلالات الحقيقية وبالتالي إعطاء الحلول الملائمة.
Keywords: الرياضيون الجزائريون -- الكراتية